THE PRINCIPLE OF INTEGRITY AND THE FRAGMENTATION OF PUBLIC PROCUREMENT - Aponte Ríos, Elvis Alexander (2023)
“Objective: Through this work, a study on the integrity of the human being and the fractionation of public procurement has been carried out. Methods: As part of the study, the authors reviewed scientific works on the subject. Results: After analyzing the contracting law 30225, its regulations and other aspects that are part of the contractual procedure, certain factors have been determined that intervene in the actions of the agents in charge of public contracting, such as: i) normative disparity; ii) incapacity of those in charge of the selection processes; and iii) acts of corruption, which put at risk the denaturalization of the norms, generating the splitting of a contract. Conclusions: The splitting of a contracting procedure corresponds more to a subjective decision where the official or servant in charge of the contracting process has the power to discern the good from the bad. The bad decision that entails an illicit conduct will generate liability. “